Statin and metformin use and outcomes in patients with castration-resistant prostate cancer treated with enzalutamide: A meta-analysis of AFFIRM, PREVAIL and PROSPER. (July 2022) - Joshua, Anthony M.; Armstrong, Andrew; Crumbaker, Megan; Scher, Howard I.; de Bono, Johann; Tombal, Bertrand; Hussain, Maha; Sternberg, Cora N.; Gillessen, Silke; Carles, Joan; Fizazi, Karim; Lin, Ping; et al.
Abstract: Background: Statins and metformin are commonly prescribed for patients, including those with prostate cancer. Preclinical and epidemiologic studies of each agent have suggested anti-cancer properties. Methods: Patient data from three randomised, double-blind, placebo-controlled, phase III studies evaluating enzalutamide (AFFIRM, PREVAIL and PROSPER) in patients with castration-resistant prostate cancer were included in this analysis. This post hoc, retrospective study examined the association of statin and metformin on radiographic progression-free survival (rPFS), metastasis-free survival (MFS), toxicity and overall survival (OS). After adjusting for available clinical prognostic variables, multivariate analyses were performed on pooled data from AFFIRM and PREVAIL, all three trials pooled, and each trial individually, to assess differential efficacy in these end-points associated with the baseline use of these medications. Results: In the multivariate analysis of the individual trials, OS and rPFS/MFS were not significantly influenced by statin or metformin use in AFFIRM or PROSPER. However, in PREVAIL, OS was significantly influenced by statin (hazard ratio [HR] 0.72; 95% confidence interval [CI] 0.59–0.89) and rPFS was significantly influenced by metformin (HR, 0.48; 95% CI 0.34–0.70). In pooled analyses, improved OS was significantly associated with statin use but not metformin use for AFFIRM+PREVAIL trials (HR 0.83; 95% CI 0.72–0.96) and AFFIRM+PREVAIL+PROSPER (HR 0.75; 95% CI 0.66–0.85). Conclusions: The association between statin or metformin use and rPFS, MFS and OS was inconsistent across three trials. Analyses of all three trials pooled and AFFIRM+PREVAIL pooled revealed that statin but not metformin use was significantly associated with a reduced risk of death in enzalutamide-treated patients. Additional prospective, controlled studies are warranted. Clinical trial registration: AFFIRM (NCT00974311 ), PREVAIL (NCT01212991 ) and PROSPER (NCT02003924 ). Highlights: No consistent association between statin/metformin and survival outcomes was found. Concomitant statin and enzalutamide use may be associated with a lower risk of death. Further prospective, controlled studies in these patients are warranted.